Review of available diagnostic options for Orthorexia Nervosa - Mateusz Grajek; Krzysztof Sas-Nowosielski (Kazimierz Wielki University, 2022)
Orthorexia Nervosa (ON) is one of the disorders with a psychological basis. The word 'orthorexia' comes from Greek, where 'orthos' means proper 'orexia' appetite. The disorder is characterized by an obsession with healthy eating, and as the disease worsens, significant food exclusions occur. In extreme cases of ON, the affected person forgoes eating any food, explaining it as a health concern. The degree of prevalence of ON in society is still highly questionable. Numerous studies indicate the prevalence of this problem, but there is no consistent data on the degree of severity of ON. The degree of severity of ON in the general population ranges from 6% to as high as 90%, such significant variation may be due to cultural reasons or a defect in the measurement tool. To date, a useful tool for diagnosing ON has not been developed, little that ON is still not treated as a separate disease or disorder. Therefore, the purpose of this paper is to present diagnostic possibilities in the form of psychometric tools that can be used in conducting scientific research and in psychological and dietetic practice.